Rancang Bangun Sistem Informasi Penjualan Berbasis Web Pada UMKM ZXID Di Kota Batam - Arif Rahman Hakim; Tukino Tukino (Prosiding, 2023)
The development of technology is currently growing, one of them is the online development, which is very fast, many companies have started to offer their spare parts online in order to make the most profit, so the competition between companies is growing "spare parts" services. Company. This is why UMKM ZXID needs to create a web marketing information system so that consumers can easily access spare parts information as they can order directly և pay for spare parts through the website. The method used is the SDLC waterfall model, which consists of needs analysis, design, software coding, testing, marketing, and maintenance. The result of this research is a web-based marketing information system that allows consumers to easily order products to order spare parts and saves employees time and money.